Natural sources, biological effects, and pharmacological properties of cynaroside - Bouyahya, Abdelhakim; Taha, Douae; Benali, Taoufiq; Zengin, Gokhan; El Omari, Nasreddine; El Hachlafi, Naoufal; Khalid, Asaad; Abdalla, Ashraf N.; Ardianto, Chrismawan; Tan, Ching Siang; Long, Chiau Ming *; Sahib, Narjis (Elsevier, 2023)
Cynaroside is a flavonoid, isolated from several species belonging to the Apiaceae, Poaceae, Lamiaceae, Solanaceae, Zingiberaceae, Compositae and other families and it can be extracted from seeds, roots, stems, leaves, barks, flowers, fruits, aerial parts, and the whole plant of these species. This paper discloses the current state of knowledge on the biological/pharmacological effects and mode of action to better understand the numerous health benefits of cynaroside. Several research works revealed that cynaroside could have beneficial effects on various human pathologies. Indeed, this flavonoid exerts antibacterial, antifungal, antileishmanial, antioxidant, hepatoprotective, antidiabetic, anti-inflammatory, and anticancer effects. Additionally, cynaroside exhibits its anticancer effects by blocking MET/AKT/mTOR axis by decreasing the phosphorylation level of AKT, mTOR, and P70S6K. For antibacterial activity, cynaroside reduces biofilm development of Pseudomonas aeruginosa and Staphylococcus aureus. Moreover, the incidence of mutations leading to ciprofloxacin resistance in Salmonella typhimurium was reduced after the treatment with cynaroside. In addition, cynaroside inhibited the production of reactive oxygen species (ROS), which reduced the damage to mitochondrial membrane potential caused by hydrogen peroxide (H2O2). It also enhanced the expression of the anti-apoptotic protein Bcl-2 and lowered that of the pro-apoptotic protein Bax. Cynaroside abrogated the up-regulation of c-Jun N-terminal kinase (JNK) and p53 protein expression triggered by H2O2. All these findings suggest that cynaroside could be used to prevent certain human diseases.